The effects of modified problem-solving therapy on depression, coping, and self-efficacy in elderly nursing home residents - Wu, Xiaoqi; Li, Jie; Zhang, Chun; Zhou, Xing; Dong, Xiaoqian; Cao, Huan; Duan, Yinglong; Wang, Sha; Liu, Min; Zhang, Qiuxiang; Xie, Jianfei (Frontiers in Psychology, 2023)
Background With the increasing trend of aging, the mental health problems of the elderly require urgent attention. Depression is a common psychological problem of the elderly, which affects their quality of life and physical health. Problem-solving therapy can effectively improve depression in the elderly, but there are few studies on problem-solving therapy for depression in the elderly in China. The purpose of this study was to evaluate the effects of modified problem-solving therapy (MPST) on depression, coping and self-efficacy in elderly nursing home residents. Methods This study was a randomized controlled trial. A total of 60 older adults from two nursing homes were recruited to participate in this study and randomly assigned to the intervention group (MPST) or the control group (usual care). The intervention lasted 8 weeks, and information on depression, coping skills, and self-efficacy was collected before the intervention, immediately after the intervention, and 3 months after the intervention. Repeated measures ANOVA was used to compare changes at multiple time points between the two groups. If the interaction effect (group * time) was significant, independent samples t-test was used to compare the differences in outcome indicators between groups at post-intervention and 3 months post-intervention. Results Compared to the control group, depression scores in the intervention group were significantly lower at the end of the intervention and remained significantly lower than the control group 3 months post-intervention (p < 0.05). Negative coping and self-efficacy in the intervention group also improved significantly at the end of the intervention, and 3 months post-intervention, while positive coping in the two groups did not differ significantly at 3 months post-intervention. Conclusion The findings of this study suggest that MPST could be beneficial in reducing depressive symptoms and enhancing positive coping and self-efficacy levels in older adults in nursing homes.